2011
DOI: 10.1038/jid.2011.139
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Regulatory T Cells of Psoriasis Patients Easily Differentiate into IL-17A-Producing Cells and Are Found in Lesional Skin

Abstract: Psoriasis is an autoimmune-related chronic inflammatory skin disease that is strongly associated with IL-23 and T helper-17 (Th17) effector cytokines. In addition, CD4+CD25(high) regulatory T-cell (Treg) function appeared to be impaired in psoriasis. CD4+CD25(high)Foxp3+ Tregs are typically considered inhibitors of autoimmune responses. However, under proinflammatory conditions, Tregs can differentiate into inflammation-associated Th17 cells--a paradigm shift, with as yet largely unknown consequences for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
341
2
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(371 citation statements)
references
References 23 publications
11
341
2
17
Order By: Relevance
“…Changes in epigeneticcontrol mechanisms may allow for switching between exhausted and activated T cell states. In addition, T reg cells can be converted into T H 17 cells in the presence of IL-6 and TGF-β 46,47 , which might underlie certain forms of autoimmunity, such as autoimmune hepatitis and psoriasis 48,49 , and CXCL11 promotes T reg cell differentiation into CXCR3 + CD4 + effector T cells, suggesting that it might be involved in the development of autoimmune encephalitis 50 . Control of T reg cell plasticity is further regulated by EZH2, a target for multiple small-molecule inhibitors in cancer trials 51 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Changes in epigeneticcontrol mechanisms may allow for switching between exhausted and activated T cell states. In addition, T reg cells can be converted into T H 17 cells in the presence of IL-6 and TGF-β 46,47 , which might underlie certain forms of autoimmunity, such as autoimmune hepatitis and psoriasis 48,49 , and CXCL11 promotes T reg cell differentiation into CXCR3 + CD4 + effector T cells, suggesting that it might be involved in the development of autoimmune encephalitis 50 . Control of T reg cell plasticity is further regulated by EZH2, a target for multiple small-molecule inhibitors in cancer trials 51 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…The presence of IL-37 in T EM cells may illustrate the possible regulation of IL-37 in T EM cells through the inhibition of Th1 activity, as revealed by our in vivo study. Considerable numbers of Tregs, characterized by high expression of Foxp3 staining, are present in the skin lesions of psoriasis and are supposed to serve as a brake for cutaneous inflammation (56). A recent study (57) demonstrated that the capacity of Tregs to enforce tolerance to harmless and self-Ags is severely ablated by their less intrinsic activity and the proinflammatory cytokine milieu in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, Bovenschen et al 96 demonstrated that this subset of Tregs from patients with severe psoriasis were more prone to differentiate into IL-17-producing cells compared to healthy controls upon stimulation. Most importantly, they found that there was a specific population of CD4 1 IL-17A 1 Foxp3 1 cells in the skin lesions, which they assume would probably contribute to the disease development.…”
mentioning
confidence: 99%